Ecological momentary assessment to explore fatigue, mood and physical activity levels in people receiving peritoneal dialysis: A study protocol. Issue 5 (September 2021) - Tarca, Brett; Jesudason, Shilpanjali; Le Leu, Richard; Ovenden, Michelle; Borlace, Monique; Meade, Anthony; Bennett, Paul N; Wycherley, Thomas P; Boyle, Terry; Ferrar, Katia E
Introduction: Fatigue is a frequent and debilitating symptom for people with end-stage kidney disease (ESKD) receiving dialysis. Ecological momentary assessment (EMA) allows real-time data capture of day-to-day and diurnal variations. EMA has been used to study haemodialysis-related fatigue but not in people receiving peritoneal dialysis who are unique in their physical, environmental and logistical characteristics. The aim of this study is to explore the real-time associations between fatigue and mood (EMA mobile application) and objective physical activity levels (accelerometry) in people with EKSD receiving peritoneal dialysis. Method: A 7-day intensive longitudinal study will be conducted. People receiving peritoneal dialysis within South Australia will be invited to participate. Five times throughout the day, participants will be prompted to answer 18 questions relating to fatigue (Visual Analogue Scale to Evaluate Fatigue Severity) and a single question for mood (Visual Analogue Mood Scale). Participants will continuously wear a GENEActiv accelerometer to capture physical activity levels during the 7-day period. At the completion of the data collection, participants will answer questions to evaluate the feasibility and acceptability of using EMA. Discussion: This study will be the first to explore the real-time relationships between fatigue, mood and physical activity in people with ESKD receiving peritoneal dialysis. Understanding the fluctuations people experience and the relationships between mood and physical activity and fatigue will inform clinical management and well-being intervention development.